The first competency-based higher education programme for midwives in the South Asian region – Pakistan. (February 2016) - Jan, Rafat; Lakhani, Arusa; Kaufman, Karyn; Karimi, Sadia
Abstract: Midwives in Pakistan and the South Asian region who complete a diploma program face many challenges for career growth and development. The absence of higher education in professional midwifery in the region has contributed to general non-acceptance and invisibility of midwifery. In response to the interest, Aga Khan University (AKU) developed bachelors program in midwifery based on the Global Standards for Midwifery Education developed by the International Confederation of Midwives (ICM) with the vision to equip midwives to provide full-scope practice, develop confidence to practice midwifery independently, become clinical leaders and contribute to the future of midwifery. The final curriculum had a balance of theory and clinical practice in order to develop a high level of clinical competence that would meet the ICM standards and guidelines. The two year bachelors program is currently in progress. The first cohort of 21 midwives graduated in 2014 and a second cohort was enrolled in 2015. There is a planning for a future graduate program in midwifery to prepare individuals for leadership roles in practice, teaching, maternal–child health provision and policy making through a master's degree in midwifery.